Value of cerebrospinal fluid examination in the diagnosis of meningitis in the newborn. Issue 5 (November 1993) - Hristeva, L; Bowler, I; Booy, R; King, A; Wilkinson, A R
Abstract : Between 1 October 1988 and 30 September 1991 the results of all 896 cerebrospinal fluid examinations from 736 neonates were correlated with clinical diagnosis, treatment, and outcome. The prevalence of fungal or bacterial meningitis in babies requiring lumbar puncture was only 0.95%. Gram staining had a sensitivity of 68% and a positive predictive value of only 46% for the diagnosis of meningitis. Primary cultures directly onto agar plates had a sensitivity of 81% and positive predictive value of 46%. Broth enrichment cultures did not improve sensitivity and were frequently found to be false positive. Empirical treatment should not be altered unless more than a few organisms are seen on Gram staining. Primary cultures are adequate for the diagnosis of fungal and bacterial meningitis. Enrichment cultures should be performed only when the Gram stain and/or cell count suggests meningitis is likely. Clinicians should be aware that diagnostic tests performed in populations with a low prevalence of disease are likely to generate many false positive results and have a low positive predictive value.